Polymorphisms in ERCC4 and ERCC5 and risk of cancers: Systematic research synopsis, meta-analysis, and epidemiological evidence - Zuo, Chunjian; Lv, Xiaolong; Liu, Tianyu; Yang, Lei; Yang, Zelin; Yu, Cao; Chen, Huanwen (Frontiers in Oncology, 2022)
The variants of DNA repair genes have been widely reported to be associated with cancer risk in the past decades. As were two crucial members of nucleotide excision repair pathway, ERCC4 and ERCC5 polymorphisms are linked with susceptibility to multiple cancers, but the conclusions were controversial. In this updated meta-analysis concerned with ERCC4 and ERCC5 single-nucleotide polymorphisms (SNPs), 160 eligible publications were identified, and we exerted the meta-analysis of correlations between 24 variants and 19 types of cancer. Venice criteria and the false-positive report probability were used to evaluate a cumulative evidence of significant associations. We conducted functional annotations for those strong associations using data from the Encyclopedia of DNA Elements (ENCODE) Project. We obtained 11 polymorphisms significantly related to changed susceptibility to 11 cancers (p < 0.05). Strong evidence was assigned to four variant-related cancer risks in Asians (ERCC4 rs744154 with bladder cancer, ERCC5 rs2296147 with esophageal cancer, ERCC5 rs17655 with laryngeal cancer and uterine cancer, and ERCC5 rs751402 with gastric cancer), moderate to six SNPs with a risk of eight cancers, and weak to nine SNPs with nine cancers. Data from ENCODE and other public databases showed that the loci of these SNPs with strong evidence might fall in putative functional regions. In conclusion, this paper summarizes comprehensive evidence that common variants of ERCC4 and ERCC5 genes are strongly associated with the risk of bladder cancer, esophageal cancer, laryngeal cancer, uterine cancer, and gastric cancer and elucidates the crucial role of the DNA repair genes in the genetic predisposition to human cancers.